3B.005 SIDS on Facebook: A qualitative descriptive content analysis of a mother's group. (14th March 2021) - Pretorius, Kelly; Choi, Eunju; Kang, Sookja; Mackert, Michael
Abstract : Background/Aims: Despite prevention efforts, many parents practice unsafe infant sleep and utilize dangerous infant sleep and monitoring devices; thus, SIDS (sudden infant death syndrome) is a leading cause of infant mortality in the US. Social media offers a unique perspective on SIDS to guide future research and prevention efforts. This study aimed to describe and analyze conversations among mothers engaged in discussions about SIDS on a Facebook mother's group. Methods: We extracted and analyzed 20 posts and 912 comments from 512 mothers who participated in a specific Facebook mother's group and engaged in conversations about SIDS. Two reviewers coded the data using qualitative descriptive content analysis. Themes were induced after discussion among researchers. Results: The theme of social support emerged. A variety of informational sources for SIDS and safe sleep were identified, as was a continuum of infant sleep practices (ranging from unsafe to safe sleep per the American Academy of Pediatrics standards). There was widespread discussion regarding infant sleep products and monitoring devices. Embedded within conversations was: (1) confusion among commonly-used medical terminology; (2) the practice of unsafe infant sleep; (3) inconsistency in provider communication about SIDS; and (4) maternal anxiety regarding SIDS. Conclusions: Mothers who participated in the Facebook group provided and received informational and emotional support regarding SIDS via this format. Future communication regarding injury prevention and safety promotion on the topic of SIDS and safe sleep should be simple, address infant sleep and monitoring devices, maternal anxiety regarding SIDS, and the common practice of unsafe sleep.